Peran Wisdom terhadap Life Satisfaction pada Lansia - Aisah Indati; Maria Goretti Adiyanti; Neila Ramdhani (Faculty of Psychology, Universitas Gadjah Mada, 2019)
Life-satisfaction is an important thing for the elderly. Elderly with all its problems such as a decrease in physical, psychological, and social conditions can feel a decrease in life satisfaction. The decrease in life satisfaction may be avoided if the elderly have a high level of wisdom. This study aimed to see the contribution of wisdom to the life-satisfaction of elderly people. The research subjects were 65 elderly people aged 60 years and over in Yogyakarta. Data retrieval was done using the adaptation of 3D-WS Ardelt (2003) scale to measure wisdom and the translation of Life Satisfaction Index Z Neugarten scale (1961) to measure life satisfaction levels. Research data were analyzed using regression analysis. The analysis found that the affective dimension of wisdom was a significant predictor of life satisfaction in the elderly (b = 0.540; p = 0.003).